Mapping the catalytic pocket of phospholipases A2 and C using a novel set of phosphatidylcholines - Caramelo, Julio Javier (2000)
A set of radioiodinatable phosphatidylcholines (PCs) derivatized with the Bolton-Hunter reagent (BHPCs) was synthesized to probe the substrate recognition and activity of phospholipases. A common feature of this series is the presence of a bulky 4-hydroxyphenyl group at the end of the fatty acyl chain attached to position sn-2. The distance between the end group and the glycerol backbone was varied by changing the length of the intervening fatty acyl chain (3-25 atoms). Except for the shortest, this chain includes at least one amide linkage. The usefulness of this series of substrates as a molecular ruler was tested by measuring the hydrolytic activities of Naja naja naja phospholipase A(2) (PLA(2)) and Bacillus cereus phospholipase C (PLC) in Triton X-100 micelles. The activity of PLA(2) proved to be highly dependent on the length of the fatty acyl chain linker, the shorter compounds (3-10 atoms) being very poor substrates. In contrast, the PLC activity profile exhibited much less discrimination. In both cases, PCs with 16-21 atom chains at position sn-2 yielded optimal activity. We interpret these findings in terms of fatty acyl chain length-related steric hindrance caused by the terminal aromatic group, affecting the activity of PLA(2) and, to a smaller extent, that of PLC. This notion agrees with the more extended recognition of aliphatic chains inside the narrow channel leading to the catalytic site in the former case. Molecular models of these substrates bound to PLA(2) were built on the basis of the crystallographic structure of Naja naja atra PLA(2) complexed with a phospholipid analogue. Docking of these substrates necessarily requires the intrusion of the bulky 4-hydroxyphenyl group inside the binding pocket and also the failure of the amide group to form hydrogen bonds inside the hydrophobic substrate channel.